Comparative analysis of competitive balance in the English Premier League and Spanish La Liga from the 2014 to 2018 seasons - Bács, B. A.; Nagy, K.; Bácsné Bába, É. (Journal of Physical Education and Sport, 2025)
In previous research comparing the English and Spanish top-flight men's football leagues, we found that several sport-specific indicators - such as win rate variance, goals scored index and the Herfindahl-Hirschman Index (HHI) index - suggest more excellent competitive balance in the English Premier League. This study expands upon that research by examining economic performance indicators, exploring which league exhibits more excellent balance in financial performance, and considering the principle of dual value creation inherent in spectator sports. Previous studies have shown that football leagues have an even competitive balance of teams so that teams of equal strength compete on the pitch, making the match's outcome difficult to predict and ensuring an exciting experience, promising more exciting matches. If this is ensured, more spectators go to the matches, increasing the interest of broadcasters and sponsors in the game and the teams. In other words, the optimal competitive balance increases aggregate revenues for individual clubs and leagues. The strength of clubs depends on their player pool, and the signing of a prominent player can easily upset the competitive balance and give his team a sporting and economic advantage. Overall, a more balanced league is also a "fairer" one. In our present study, we intend to examine the English and Spanish championship seasons between 2014 and 2018 to identify which of these two leagues is more balanced when clubs are compared and analysed in terms of the revenue they receive from the leagues, their value of the player pool and their player transfer activity. When selecting the period for our study, we intended to avoid the influence of the COVID-19 epidemic, so we chose the seasons when the league competitions were still held "regular". Regarding the value of the roster in these two leagues, the difference between the market values of the clubs in the top, middle and bottom "houses" of the championship is more substantial in the Spanish league than in the English one. Regarding revenue from national leagues, the Premier League features a more balanced distribution of money than La Liga. Concerning the nature of player transfers, the top-flight English football aligns more closely with an ideal distribution than the Spanish one. Economic and sport-specific metrics indicate that the English top flight is more balanced than the Spanish, and a more balanced league has a higher chance of an uncertain outcome, which could be a demand factor. Today, the globalisation of sport is an incentive to look at these factors.